Gambaran Fakor Dukungan Keluarga Yang Melarbelakangi Kepatuhan Kunjungan Masa Nifas (PNC) Pada Ibu Nifas Di Puskesmas Wire Kabupaten Tuban - Mariyatul Qiftiyah (Jurnal Kesehatan dr. Soebandi, 2019)
Post partum visit is a visit made by postpartum health workers during the postpartum period. But the phenomenon that occurs in the community is often only twice or one visit during post partum. Therefore, the researcher aimed to identify the family support factors that lay behind the compliance of postpartum visits at the Tuban Wire Health Center. This research uses descriptive method. The population in this study were all postpartum mothers who performed postpartum visits at the Tuban Wire Health Center. By using saturated sampling technique, it was found that 30 postpartum mothers were sampled. Data collection techniques using a closed questionnaire, then calculated using a proportion test. Based on the results of the study showed that half of the post partum mothers who received adequate family support (50%) and most of the postpartum mothers did not comply to visit during the postpartum period (66.66%). Based on the above results, it is expected that in addition to health workers, family support is also needed as motivation for postpartum mothers to conduct postpartum visits in accordance with government programs that have been determined.